PENGARUH SUMBER DANA DAN TINGKAT KOLEKTIBILITAS KREDIT TERHADAP ALOKASI KREDIT DAN KINERJA KEUANGAN BANK PERKREDITAN RAKYAT DI SULAWESI SELATAN - TANDI, ASRIN; RATNAWATI, TRI; MALIK, TAJUDDIN (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2018)
ABSTRACTThis study aims to identify and analyze: (1) Sources of funds have a significant effect on credit allocation, (2) Sources of funds have a significant effect on Financial Performance, (3) Credit collectability has a significant effect on Credit Allocation, (4) Credit collectability has a significant effect on financial performance, (5) credit allocation has a significant effect on financial performance. The data used in this study are primary data and secondary data. The population of this study is the Rural Bank in South Sulawesi, with a sample of 200 respondents as employees of the Rural Bank. Processing and Analysis of data using the Structural Equal Modeling (SEM) program, to find out the Financial Performance of Rural Banks is used 3 (three) variables: Fund Source, Credit Allocation and Credit Collective Level. The results of the study show that: (1) Sources of funds have a significant effect on credit allocation, (2) Sources of funds have a significant effect on Financial Performance, (3) Credit collectability has a significant effect on Credit Allocation, (4) Credit collectability has a significant effect on financial performance , (5) Credit allocation has a significant effect on the financial performance of Rural Banks in South Sulawesi.Â Keyword : Sumber Dana, Alokasi Kredit, Tingkat kolektibilitas dan Kinerja Keuangan.